Lifeguard - Patterson, James, 1947-; Gross, Andrew, 1952-; Campbell, William, 1959- (Westminster, MD : Books on Tape, 2005)
Everything is going right for lifeguard Ned Kelley. He is involved with Tess, the most beautiful woman he has ever seen and what's more, a million dollars is within touching distance; his share of the score for the robbery of some world-class art. All he has to do is trigger alarms to throw the cops off the scent. But when Tess is brutally murdered and the others involved in the robbery are massacred, Ned is the prime suspect. He has been set up.
Compact disc.
Read by Billy Campbell.
Keywords: Lifeguards -- Fiction; Sound recordings; Fiction; Thriller fiction